THE DYNAMICS OF VIOLENCE AGAINST DOMESTIC WORKERS: A REVIEW OF POSITIVE LAW AND FIQH JINAYAH - Djauhar, Aisyah; Haq, Islamul; Saidah, Saidah; Wahidin, Wahidin; AR, Zulfahmi (Indonesian Journal of Shariah and Justice, 2025)
Violence against domestic workers is a complex social and legal issue, reflecting the imbalance of legal protection and human values. This study aims to examine the dynamics of violence against domestic workers through the approach of the Minister of Manpower Regulation (PERMENAKER) No. 2 of 2015 and the Law on the Elimination of Domestic Violence (PKDRT Law). Meanwhile, Jurisprudence underlines violence against domestic workers as an act of wrongdoing, which is a jarimah ta'zir. This research was conducted using the literature method, through several stages: (1) Problem Identification, which recognizes the issue of violence against domestic workers from the perspective of positive law and Fikih Jinayah; (2) Data Collection, involving legal literature, religious documents, and case studies; (3) Data Analysis, using a descriptive-analytical approach to compare the views of positive law and Fikih Jinayah on violence; and (4) Conclusion, which integrates the findings from both perspectives to provide strategic recommendations.